A numerical comprehensive evaluation of a micro-type plate autothermal methanol steam reformer with different channel configurations. (23rd November 2022) - Chen, Zhiling; Jian, Yi; Yan, Jiahan; Dong, Fei; Yin, Bifeng
Highlights: The fractal channel with n β > 1 can promote the MSR to proceed forward; The branch enhances the mixing effect, thereby improving the methanol conversion. The reformer with PTC channel has the highest performance of heat and mass transfer. Abstract: Hydrogen production from methanol steam reforming (MSR) is one of the solutions of mobile hydrogen source for fuel cell. In this paper, a three-dimensional numerical model of a micro-type plate autothermal methanol steam reformer with different channel configurations is established. The effects of the Point-Grow-Naturally (PGN), Point-To-Line (PTL) and Point-To-Circle (PTC) fractal channel designs and operation conditions on the heat and mass transport between the combustion chamber and catalytic chamber are investigated and compared with parallel channels. The results show that the existence of branches enhance the mixing effect of reactants, but increases the pressure drop at the same time. When the branch ratio and the branch number satisfy the mathematical relationship n β > 1, the fractal channel can be equivalent to a gradually expanding channel, which is conducive to MSR in the direction of volume increase. In all configurations, PTC has more uniform temperature distribution, better heat transfer performance, low pump power consumption and higher methanol conversion.